Pilot Test of Co-pyrolysis Characteristics of Wet Sewage Sludge and Sawdust in an External Heating Moving Bed. (May 2017) - Zhu, Jinjiao; Wan, Long; Chen, Haijun; Zhu, Yuezhao; Yang, Li
Abstract: The process of traditional sludge treatment is complex and high energy consumption. A drying and pyrolysis integration technology of high moisture sludge was put forward. On the basis of experimental study, the pilot study was carried out. Co-pyrolysis characteristics of wet sewage sludge and sawdust for syngas production was studied in this paper. The thermogravimetric analysis showed that the addition of sawdust accelerated the pyrolysis reactions. Moreover, the weight loss and mass loss rate also increased with sawdust proportion augmenting. The mixture with 60 wt. % wet sewage sludge and 40 wt. % sawdust was pyrolyzed in a self-designed external heating moving bed pilot scale device with the capacity of 200 kg/h. Results showed that with pyrolysis carrying out, H2 content was increasing from 33.62% to 47.71% and the volumetric concentration of fuel gas including was also gradually increasing. The heat value of pyrolysis gas mainly distributed between 15∼18 MJ/ Nm 3, which is appreciable for industrial applications and provides a new idea for direct pyrolysis of sewage sludge.